Flexural Capacity and Ductility of HPS-70W Bridge Girders - Yakel, Aaron J.; Mans, Patrick; Azizinamini, Atorod (Engineering Journal, 2002)
The development of High Performance Steel (HPS), which boasts high yield strengths (70 and 100 ksi), while maintaining ductility and toughness combined with an available weathering finish offers many potential opportunities to steel bridge design. Many of these benefits have yet to be realized due to the limitations in design specifications placed on the use of steels with yield strength above 50 ksi. This paper reports on the experimental results and associated finite element analysis of four girders intended to address the limitations placed on girders in negative bending, e.g., girders spanning over a pier in multiple span bridges. All of the girders tested were able to attain their predicted strength as determined using the AASHTO LRFD Bridge Design Specifications (AASHTO, 1998). However, the compact section tested did not exhibit the amount of ductility implied by the equations. Based on the results of the tests and analyses performed, the limitations with regards to strength could be removed while the compact provisions allowing moment redistribution may require additional investigation.